2014
DOI: 10.1186/s40536-014-0005-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of test-taking motivation for students’ performance in low-stakes assessments: an investigation of school-track-specific differences

Abstract: Background: Low-stakes assessments do not have consequences for the test-takers. Currently, motivational research indicates that a lack of test-taking motivation can decrease students' performance in low-stakes assessments. However, little research has explored the domain-specific and situation-specific aspects of motivation simultaneously. Research examining differences in test-taking motivation among students in different types of schools is also limited. Our study therefore addressed the motivational determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 23 publications
0
35
0
3
Order By: Relevance
“…Personality measures of agreeableness and conscientiousness have also proven to be positively related to test-taking effort (DeMars et al 2013). In a study by Penk et al (2014), invested effort, that is, the self-reported willingness to engage with test items, was explained by individual differences in task-irrelevant cognition, specifically distraction.…”
Section: Person Levelmentioning
confidence: 99%
“…Personality measures of agreeableness and conscientiousness have also proven to be positively related to test-taking effort (DeMars et al 2013). In a study by Penk et al (2014), invested effort, that is, the self-reported willingness to engage with test items, was explained by individual differences in task-irrelevant cognition, specifically distraction.…”
Section: Person Levelmentioning
confidence: 99%
“…The first one is domain specific motivation, and the other one is situation specific motivation. Domain specific motivation refers to the success motivation for a specific area (eg; mathematics and science) while situation specific motivation refers to the success motivation to perform well in a given situation or a particular exam (Eklöf, 2006a(Eklöf, , 2006b(Eklöf, , 2007Penk, Pöhlmann, & Roppelt, 2014). Since exam motivation (Schunk et al, 2008) is an active process to initiate and sustain the goal-oriented activity, it is a special type of academicmotivation.…”
Section: öNeriler Ve Sınırlılıklarmentioning
confidence: 99%
“…Since exam motivation (Schunk et al, 2008) is an active process to initiate and sustain the goal-oriented activity, it is a special type of academicmotivation. For this reason, exam motivation goes into these condstage of academic motivation, because taking an exam is a special case for the students (Penk, Pöhlmann, & Roppelt, 2014). Baumert and Demmrich (2001) describe test motivation as "trying to study for exams and showing willingness" (Penk, Pöhlmann, & Roppelt, 2014).…”
Section: öNeriler Ve Sınırlılıklarmentioning
confidence: 99%
See 2 more Smart Citations